THE EFFECT OF USING NARRATIVE TEXT ON LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS AT SMP NEGERI 7 TARAKAN - Rangga, Agnesi; Rafiqa, Syarifa; Nurdiana, Nurdiana (Borneo Journal of English Language Education, 2024)
The purpose of this study was to determine how the use of narrative texts affects the learning outcomes of eighth grade students at SMP Negeri 7 Tarakan. This study used a qualitative approach. Students from grades VIII-9 were used as the experimental group, VIII-7 and VIII-8 were used as the control group. Observation, interviews, documentation, and learning tests were the methods used to obtain data. The results showed that, compared to the control group, students who used narrative texts had better reading and writing skills. The narrative text-based approach motivated students to be more active in learning and better understand their culture. The theories of constructivism and experiential learning were supported by this study. To improve the quality of English learning, it is recommended that narrative texts be included more in the curriculum.Keywords: Narrative text, learninng outcomes